Clinician's Guide to Adult ADHD Comorbidities : Case Studies - Sadek, Joseph (Springer International Publishing : Imprint: Springer, 2017)
The diagnosis and management of ADHD co-occurring with other disorders such as anxiety, depression and personality disorders remain major challenges for clinicians treating all age groups. This book guides clinicians through each step in the diagnosis and management of the comorbidities of adult ADHD on the basis of essential case studies describing psychiatric disorders that frequently occur with ADHD. Each case includes a diagnosis section and management section and is accompanied by questions and answers concerning the most important aspects in diagnosing and managing both ADHD and the comorbid disorders. Drawn from actual clinical encounters, the case studies also feature ample current and valid references.
Keywords: Medicine.; Psychopharmacology.; Clinical psychology.; elektronické knihy; electronic books